Mathematics in Cryptography and Its Applications in Cybersecurity - Isnaini, Uha; Qomariasih, Nurul; Amiruddin, Amiruddin; Tantrawan, Made; Arizal, Arizal; Ernanto, Iwan; Adiati, Nadia Paramita Retno; Indarsih, Indarsih; Yasa, Ray Novita; Wijayanti, Indah Emilia; Indarjani, Santi; Salmah, Salmah; Ulfa, Septia; Hartanto, Ari Dwi; Amelia, Fetty (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
The growing prevalence of cyber threats and attacks poses significant risks to the security of personal data and the integrity of sensitive information worldwide. Cryptography plays a vital role in establishing strong cybersecurity defenses, and the development of robust cryptographic algorithms is essential for protecting data against cyber-attacks. This workshop aimed to enhance participants’ understanding of the mathematical foundations of cryptographic algorithms and equip them with practical skills to identify and mitigate cyber threats. It also introduced innovative educational tools, including an Augmented Reality (AR) application for teaching classical cryptography and a Game-Based URL Phishing Education application. A total of 110 participants attended and completed the pre-test. The post-test measured knowledge gained during the workshop, and an accompanying survey gathered feedback on its effectiveness and identified areas for improvement. Overall, the workshop successfully achieved its objectives by educating participants on cryptography in the Internet of Things (IoT), increasing awareness of social engineering, introducing cryptographic tools from ancient to modern times, and exploring the principles of quantum cryptography.